Gendered Emotional Labour in Academia: Not Receiving but Expected to Give - Scolnic, Galina; Halliday, Jennifer (Atlantis, 2024)
The authors share their reflections in the aftermath of the roundtable Emotional Labour in Academia that took place during the Women’s and Gender Studies et Recherches Féministes (WGSRF) 2023 conference. Although each participant at the roundtable had a unique positionality, they had experiences to share as women in academia who desire to do their work well without exhausting themselves in the process. This paper does not restate all that was said during the roundtable event but shares what we have learned collectively and individually and further expresses the authors’ desire for more discussion on similar topics wherein we learn with and from each other about how to foster spaces of care and solidarity with one another.